Stop Vape And Cigaretesn: Community Service For A Healthy, Nicotine Free Generation At SMK Al-Washliyah 3 Medan - Zola Efa Harnis; Ainil Fithri Pulungan; Zulmairani Zulmairani (International Journal Of Community Service, 2026)
The use of conventional cigarettes and e-cigarettes (vapes) among adolescents is a public health issue that requires serious attention. Poor understanding of the dangers of nicotine and the perception that vapes are safer than cigarettes are factors driving the increased use of nicotine products among students. This community service activity aims to increase the knowledge and awareness of students at SMKS Al Washliyah 3 Medan regarding the dangers of cigarettes and vapes, their nicotine content, and their impact on health through scientific evidence-based education. The activity was implemented through a participatory educational approach, including health education, presentations, interactive discussions, and refusal skills training for students who are tempted to use cigarettes and vapes. The target group of the activity was adolescent students at SMKS Al Washliyah 3 Medan. Educational materials covered the differences between cigarettes and vapes, the harmful substances contained in nicotine products, the impact of nicotine on adolescent brain development, the risks of short-term and long-term health problems, and strategies for developing a healthy lifestyle without nicotine. The results of the activity showed an increase in students' understanding of the risks of cigarette and vape use, particularly regarding nicotine content and the potential for dependence. Through discussion sessions, students also began to understand that vaping is not a safe product, but rather carries health risks and can be a gateway to conventional smoking. This activity also encouraged students to develop positive attitudes toward rejecting the use of nicotine products and supporting the creation of a healthy, smoke-free school environment. This community service activity contributed to improving adolescent health literacy through a promotive and preventative approach based on evidence-based education. Continuous education about the dangers of smoking and vaping in the school environment is expected to foster a more health-conscious, productive, and nicotine-free young generation.